MAGNETIC RESONANCE SEMIOTICS OF BREAST CANCER - S. V. Serebryakova; G. E. Trufanov; E. A. Yukhno (ABV-press, 2014)
Breast cancer (BC) that is the most common malignancy in women presents an indubitable threat to their life and health. The basis for this investigation was magnetic resonance imaging (MRI) data of 203 women with histologically verified malignan- cies. The patients' mean age was 53±10.2 years. The paper describes the magnetic resonance semiotics of BC; the authors have developed criteria for dynamic contrast-enhanced magnetic resonance mammography used in the differential diagnosis of nodules.Due to high soft-tissue contrast, the use of thin sections, and the possibility of examining in any projection, MRI allows one not only to accurately visualize a pathological mass as compared with X-ray mammography or ultrasound study, but also to characterize its vascularization, which is a major criteria for the differential diagnosis of benign and malignant breast nodules.